Cloud-Powered Multimodal AI in Patient Care: A Technical Analysis - Pramod Malikarjun Halapeti, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive article explores the transformative impact of cloud-native multimodal AI systems in healthcare, examining their implementation architecture, technical benefits, and future considerations. The article investigates how distributed computing architectures enable seamless voice recognition, medical imaging, and sensor data analytics integration for enhanced patient care. The article demonstrates significant improvements in resource utilization, data processing capabilities, and clinical outcomes through cloud-native implementations. The article encompasses various aspects, including infrastructure components, security measures, performance advantages, and clinical applications, while also addressing the technical challenges and evolutionary paths in healthcare cloud computing.
Keywords: Cloud-Native Healthcare; Multimodal AI Systems; Healthcare Data Integration; Clinical Decision Support; Healthcare Security Framework